A estética e a circulação de Fake News durante a campanha presidencial de 2018: desafios à epistemologia da informação - Morais Filho, Luís Carlos (2020)
It is intended to present, through this work, an epistemological discussion about the concepts of information, message and speech and its application to the analysis of objects belonging to the sphere of discursive and aesthetic activities involved in the dissemination of fake news through visual and audiovisual messages during the campaign period for the 2018 Brazilian presidential elections. The theoretical contributions chosen are mostly informational, with greater emphasis on the works of Claude Shannon (1964) and Luciano Floridi (2011; 2019). Authors from the field of aesthetics who, in some way, participated in the reflection on the concepts of information, message and discourse in their specific field, such as Umberto Eco (1992; 1997; 2012), Abraham Moles (1978) and Max Bense (2003) are also included in the scope of the reflections made. We work with the hypothesis that, given the correct levels of abstraction, it is possible to analyze the production and distribution of messages with false content mediated in the context of social networks and to identify the factors that enable the construction of the sensation of verisimilitude necessary for their efficiency.